2010
DOI: 10.4137/sart.s5414
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding DWI among Bar-room Drinkers: Strategies and Predictors

Abstract: We examined the prevalence and predictors of 11strategies to avoid driving when feeling intoxicated among 561 bar-room patrons in two medium-sized Maryland communities. Logistic regression analyses identified demographic, behavioral, and attitudinal predictors of avoidance strategies and interactions among predictors. Overall, 89% reported one or more DWI avoidance actions in the past year, and 38% reported driving intoxicated during that time. Average frequencies of avoidance behavior and intoxicated driving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
(87 reference statements)
1
4
0
Order By: Relevance
“…Despite these results, it is worrying that a fairly high percentage (35.6%) admits that it happened at least once to drive after consuming alcohol. The outcomes obtained, regarding the confidence in driving safely when intoxicated, are similar to those of other recent studies (Alonso et al, 2015; Caudill et al, 2010: 46). However, according to the same studies one disturbing finding is that the level of confidence in driving safely when intoxicated was positively and significantly related to drinking level and driving intoxicated, consistent with another California bar-room study conducted much earlier, in 1990.…”
Section: Romanian Drink-driving Offender Profilesupporting
confidence: 88%
“…Despite these results, it is worrying that a fairly high percentage (35.6%) admits that it happened at least once to drive after consuming alcohol. The outcomes obtained, regarding the confidence in driving safely when intoxicated, are similar to those of other recent studies (Alonso et al, 2015; Caudill et al, 2010: 46). However, according to the same studies one disturbing finding is that the level of confidence in driving safely when intoxicated was positively and significantly related to drinking level and driving intoxicated, consistent with another California bar-room study conducted much earlier, in 1990.…”
Section: Romanian Drink-driving Offender Profilesupporting
confidence: 88%
“…Some argue that the relationship between designated drivers and passenger consumption is unclear, in that heavier drinkers are more likely to avoid legal consequences of driving under the influence by strategies other than a designated driver such as: taking a cab, walking, or simply relying on a friend who has had less to drink (Caudill, Rogers, Howard, Frissell, & Harding, 2010). However, one laboratory study (Rivara et al, 2007) found that the use of a designated driver resulted in almost half of the participants (ages 21–34) drinking more on that occasion than they usually drink.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, by far the largest percentage of AT users were White males ages 18–35 ( Caudill et al, 2010 , Elamet al, 2006 ). There are several possible reasons why non-White patrons appear to underutilize these programs.…”
Section: Resultsmentioning
confidence: 99%
“…The research literature focuses on a variety of AT programs: safe ride shuttles; free or subsidized taxi, ridesharing, and public transportation; and voluntary or paid designated driver programs ( Molofet al, 1995 , Boots and Midford, 1999 , Caudill et al, 2000 , Hardinget al, 2001 , Sarkaret al, 2005 , Elamet al, 2006 , Rothschildet al, 2006 , Decinaet al, 2009 , Meece, 2009 , Nielson and Watson, 2009 , Caudill et al, 2010 , Gieck and Slagle, 2010 , Sprattler, 2010 , Chan, 2011 , Rivaraet al, 2012 , Weber, 2014 , Tiegs, 2015 , New Jersey Opinion, 2016 , National Academy of Sciences, Engineering, and Math (NASEM), 2018 , Jarchow, 2018 , Tavern League of Wisconsin SafeRide Program, 2019 .). These programs vary by the types of services provided and marketing and incentive strategies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation